A imagem da escuta: os sites person-to-person e os compositores heterônimos - Rodrigues, Rodrigo Fonseca e (2007)
The main issue of this thesis is concerned to the listening and it's compositions in view of the experimental ways of frequentation of the architecture person-to-person in the internet. They will be approached, as empirical corpus, practices of sonorous compositions spread through site-programs like soulseek.org and known as bootleg mash ups. The research tries to demonstrate the difficulties coming from the specutations of the thought when dealing with the investigation how the sensations in the listening,make some contagious, encouraged by collective affects linked to the temporalities of the technology and the musical creation. The conceptual basis of this thesis leans on the approximation among the echoing ideas of F. Nietzsche, Gabriel Tarde, Henri Bergson, F. Pessoa, Gilles Deleuze and F. Guattari. The purpposal is to discuss, from the conceptions that these authors brought to the problem of the imagem in the thought, what changes about the sensation of listening when the image of the thought changes.In such a way this work adopts the contribution of the "thought of the haecceitas", trying to re-imagine the creative virtualities of the Time in the composition of the musical listening. Accorded to this conception, instead of abiding by the practice of cutting and pastting sonorous elements, the desktop's composer will need to invest previously in an experimental economy of rhythms and images of the Time to potencialize the sensations in the listening. From this premise, it is asserted that the creative performances of musical listening, stimulated by the ways of conviviality into the sites peer-to-peer, need to interfere in the regimes of perception, sense and the image that the subjectivity aquires in the stereotyped cadences of the internet. Such practices present themselves as an heteronymic poetical activity, with an invenctive resistence to the recent technological processes of subjectivation. To achieve this level, the compositional listening needs to go beyond the reccuring stable regimes of the sound, the sign, the space, the phenomenon, the sense, the techinque and the musical logos in the transcndentalimage of thought. From this creative battle in a saturated enviroment of axioms, the musical composition faces up the problem of retitute singular in the sensation, to transduce the wills and to make a contagious of the sensivity virtualities into the thought of the listening